Spatial microheterogeneity in the valence band of mixed halide hybrid perovskite materials. Issue 32 (2nd August 2022) - Erbing, Axel; Philippe, Bertrand; Park, Byung-wook; Cappel, Ute B.; Rensmo, Håkan; Odelius, Michael
Abstract : Microheterogeneity in valence band maximum of hybrid perovskites with mixed I/Br composition. Theoretical calculations show that trends in hard X-ray photoelectron spectroscopy with overall composition are related to variations in local environment. Abstract : The valence band of lead halide hybrid perovskites with a mixed I/Br composition is investigated using electronic structure calculations and complementarily probed with hard X-ray photoelectron spectroscopy. In the latter, we used high photon energies giving element sensitivity to the heavy lead and halide ions and we observe distinct trends in the valence band as a function of the I : Br ratio. Through electronic structure calculations, we show that the spectral trends with overall composition can be understood in terms of variations in the local environment of neighboring halide ions. From the computational model supported by the experimental evidence, a picture of the microheterogeneity in the valence band maximum emerges. The microheterogeneity in the valence band suggests that additional charge transport mechanisms might be active in lead mixed halide hybrid perovskites, which could be described in terms of percolation pathways.